Problems and prospects of development of the shearing economy of the Russian Federation - Svetlana V. Boyko; Marina I. Sukhinina (Муниципалитет: экономика и управление)
Introduction. The article is devoted to the analysis of the carsharing economy in Russia with a focus on the most widespread segment - carsharing. Changing public attitudes towards car ownership and growing interest in resource sharing create new conditions for the study of carsharing as a social phenomenon. In conditions of economic instability, carsharing may become a more affordable option for many people, which makes its study relevant in terms of economic efficiency. The study of carsharing is important for understanding current trends in transportation and their impact on society and the economy. The conducted research is based on the data on the dynamics of the growth of carsharing in the Russian Federation, the forecast of its development until 2025, as well as the analysis of advantages and disadvantages of different types of carsharing. Methods. The study was carried out with the help of general scientific methods, including the analysis of authors' works, synthesis and comparison of information, application of system-functional and complex approaches. Results. The research has shown that the carsharing economy in Russia demonstrates steady growth, especially in the carsharing segment. By 2025, the total volume of the sharing economy is expected to exceed 2 trillion rubles. The article discusses the advantages of the sharing economy, such as reducing resource consumption, saving money and improving the environmental situation, and the disadvantages, which include possible problems with the safety and reliability of services. Conclusions. Carsharing in Russia has great potential for further development. In the Russian Federation, the development of carsharing has become a priority in the context of increasing demand for mobility and environmental responsibility. However, there are a number of problems that hinder the development of this sector: limited legislation, lack of infrastructure, and safety issues. Thus, the development of sharing in Russia requires: improvement of legislation, including the legal framework for sharing companies; development of infrastructure, including expansion of the bicycle rental network and creation of new parking zones; improvement of safety of sharing participants, including through educational campaigns and control by the authorities.